Variation of Ethnomycological Knowledge in a Community from Central Mexico - Eribel Bello-Cervantes; Alexander Correa-Metrio; Adriana Montoya; Irma Trejo; Joaquín Cifuentes Blanco (Journal of Fungal Diversity, 2019)
We analyze the effects of the ethnomycological knowledge depending on the age range of its users and how far their homes are from the forest areas. As a study model, the traditional mycological knowledge of San Pedro Tlalcuapan SPT, in Central Mexico was used. During 2017, 135 semi-structured interviews were conducted with people of three age ranges and living in three areas of the community located at different distances from the forest. Data was analyzed using descriptive statistics and analyses of non-metric multidimensional scaling, which were then applied to calculate two indices. The effect of age and origin of the individuals on bio-cultural relevance was assessed using multiple linear regression models.Fifty species of edible wild mushrooms were registered, those mentioned most often were of the Russuladelica complex., Amanita basii and Boletus aff. edulis. Ninety-five percent of the people interviewed consumed wild mushrooms on average two times a week, while 57% collected them. Wild mushrooms are mainly recognized for their food and ecological importance. Ordination and regression analyses show that people closest to the forest, as well as older people, are able to identify more of the wild mushrooms and have greater bio-cultural mushroom awareness. Results show that there is a risk that traditional knowledge about wild mushrooms will disappear, since it is only popular in a part of the community and only at some age ranges, indicating that there is a disconnect in the transfer of knowledge.
Keywords: Ethnomycological Knowledge